Prestripping section of the MILAC accelerator based on the principle of alternating-phase focusing with the moving bunch center - Bomko, V.A.; Mazalov, Yu.P.; Meleshkova, Yu.V.; Kobetz, A.F.; Rudyak, B.I. (Вопросы атомной науки и техники, 1999)
The main task facing the personnel of the linear accelerator of multicharged ions (MILAC) at the NSC KIPT was carrying out the fundamental investigations in the field of nuclear physics and material engineering.